2020
DOI: 10.1111/sji.12919
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of maternal psychological stress during pregnancy for the risk of asthma in the offspring

Abstract: The British Lung Foundation reports that over 12% of the UK population-eight million people-have been diagnosed with asthma during their lifetime, and that there are 160 000 new cases a year. 1 Symptoms vary from occasional mild breathlessness through to frequent debilitating bouts of severe breathing problems. One of the most accepted mechanisms of asthma pathogenesis implicates the actions of cytokines produced by T-helper 2 (Th2) cells, but the cause of asthma remains unknown. Known risk factors for the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…It has also been shown that polymorphisms and mutations in specific sites of this gene has correlation with increase in TGF-β expression in asthma patients 31 , which is a well-known mediator that leads smooth muscle proliferation and airway remodeling. Regarding the epigenetic regulation of NR3C1 , maternal stress during pregnancy, caused increased methylation in the umbilical cord blood mononuclear cells that cause decreased GR expression in the child, which may affect cytokine production and treatment response in the childhood asthma 32 .…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that polymorphisms and mutations in specific sites of this gene has correlation with increase in TGF-β expression in asthma patients 31 , which is a well-known mediator that leads smooth muscle proliferation and airway remodeling. Regarding the epigenetic regulation of NR3C1 , maternal stress during pregnancy, caused increased methylation in the umbilical cord blood mononuclear cells that cause decreased GR expression in the child, which may affect cytokine production and treatment response in the childhood asthma 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Epigenetics mechanisms, such as DNA methylation, can modify the immune response across the lifespan in response to maternal stress during pregnancy ( Al-Hussainy and Mohammed, 2021 ). T cell differentiation is controlled by epigenetic mechanisms that regulate Th1 and Th2 identity.…”
Section: Maternal Stress and Fetal Programming Of Immune Responsementioning
confidence: 99%
“…T cell differentiation is controlled by epigenetic mechanisms that regulate Th1 and Th2 identity. Prenatal maternal psychological stress can affect the epigenetic profile of human T cells in a way that affects cytokine production ( Al-Hussainy and Mohammed, 2021 ). Cao-Lei et al (2014) examined the DNA methylation patterns in T cells of offspring of women exposed to the 1998 Quebec ice storm and found that the genes most commonly methylated are involved in immune system pathways ( Cao-Lei et al, 2014 ).…”
Section: Maternal Stress and Fetal Programming Of Immune Responsementioning
confidence: 99%
“…Regarding the epigenetic regulation of NR3C1, maternal stress during pregnancy, caused increased methylation in the umbilical cord blood mononuclear cells that cause decreased GR expression in the child, which may affect cytokine production and treatment response in the childhood asthma. 32 FKBP5 and asthma FKBP5 or FK506-binding protein 51, is a member of immunophilin protein family that has peptidyl-prolyl isomerases to catalyze isomeric shape of proline amino acid and thus, act as cochaperon to assist protein folding in various proteins. Increased levels of protein is found in central and peripheric airway brushings of severe asthma patients comparing to healthy subjects.…”
Section: Nr3c1 and Asthmamentioning
confidence: 99%